Perbedaan Status Kebugaran Berdasarkan Status Gizi, Aktivitas Fisik, dan Asupan Gizi Pada Mahasiswi Gizi Fkm UI - Komala, Ramadhana; Achmad, Engkus Kusdinar (Universitas Aisyah Pringsewu (UAP) Lampung, 2019)
The low fitness levels was a risk factor for cardiovascular disease. The primary purpose of this cross-sectional study design that aims to identify differences in fitness status based on the status of nutrition, physical activity, and nutrition. In this study, 156 female students of Nutrional Sciences FPH UI were aged 18-22 years. Physical fitness was measured using YMCA 3-minute step test method. The results shows that based on the fitness tests are 67.9% female students classified as unfit. Variables that have significant differences in this study were percent body fat, intake of protein, fat, vitamin B2, and zinc/Zn. Normal percent body fat, intake of protein, fat, vitamin B2, and zinc /Zn sufficient to improve physical fitness.